Insights from the single-cell level: lineage trajectory and somatic-germline interactions during spermatogenesis in dwarf surfclam Mulinia lateralis - Yajuan Li; Huilan Wei; Xiaoting Dai; Lijing Zhang; Liangjie Liu; Xiaomei Chen; Tian Liu; Ya Shu; Yaxin Yang; Shi Wang; Zhenmin Bao; Lingling Zhang (BMC Genomics)
Abstract Background Spermatogenesis is a complex process of cellular differentiation that commences with the division of spermatogonia stem cells, ultimately resulting in the production of functional spermatozoa. However, a substantial gap remains in our understanding of the molecular mechanisms and key driver genes that underpin this process, particularly in invertebrates. The dwarf surfclam (Mulinia lateralis) is considered an optimal bivalve model due to its relatively short generation time and ease of breeding in laboratory settings. Results In this study, over 4,600 testicular cells from various samples were employed to identify single-cell heterogeneity on a more comprehensive scale. The four germ cell populations (spermatogonia, primary spermatocytes, secondary spermatocytes, and round spermatids/spermatozoa) and three somatic populations (follicle cell, hemocyte, and nerve cell) were characterized. The four types of germ cells exhibited disparate cell cycle statuses and an uninterrupted developmental trajectory, progressing from spermatogonia to spermatids/spermatozoa. Pseudotime analysis indicates that gene expression, translation, ATP metabolic process, and microtubule-based process are involved in the transition of germ cell types. Weighted gene coexpression network analysis (WGCNA) identified four modules corresponding to the four types of germ cells, as well as key transcription factors (e.g., MYC, SREBF1, SOXH) that may play a critical role in these cell types. Furthermore, our findings revealed that there is extensive bidirectional communication between the somatic cells and the germline cells, including the FGF and TGF-β signaling pathways, as well as other ligand-receptor pairs, such as NTN1-NEO1 and PLG-PLGRKT. Conclusions This study provides a comprehensive single-cell transcriptome landscape of the gonad, which will contribute to the understanding of germ cell fate transition during spermatogenesis, and the development of germ cell manipulation technologies in mollusks.